Emotional intelligence: a competitive advantage for tourism and hospitality managers. Issue 4 (4th July 2022) - Stoyanova-Bozhkova, S.; Paskova, T.; Buhalis, D.
ABSTRACT: The purpose of this paper is to provide a better understanding of tourism and hospitality management through exploring the perceptions of and the application of emotional intelligence (EI) in the practices of managers. The effect of EI on improving business performance is widely acknowledged in business and management studies. However, there is limited research in the context of tourism and hospitality industries. The paper contributes to the literature through a qualitative study of the perceptions and experiences of middle-level managers. Data was collected through semi-structured in-depth interviews conducted in tourism and hospitality organisations in the UK. The findings of the study reveal that EI can have a positive contribution to improving staff satisfaction, motivation and overall business productivity. They highlight the importance of building quality relationships among staff and the critical role middle management has in an organisation. Based on the finding from the qualitative inquiry, the authors propose a model conceptualising the role of managers' EI in creating a competitive advantage for the organisation. Practical implications are discussed and recommendations for further research are provided.